(untitled) (Medico Legal Update, 2021)
Knowledge of the anatomy of liver is a prerequisite for a complete understanding of the mechanics of diagnostic imaging and minimally invasive surgical approaches. So the aim of the study is to carry out the morphological feature of right lobe, left lobe, caudate lobe, quadrate lobe and surfaces of liver. This is retrospective observational study done on 75 human livers irrespective of age and sex in Department of anatomy, Smt. B.K. Shah Medical Institute and Research Center, Vadodara, Gujarat. The livers were studied for morphological variationsuch as accessory fissure, accessory mini lobe, Quadrant lobe with tongue like projection, Pons hepatis connecting left lobe with quadrate lobe, Riedel’s lobe present, Narrow and elngated left lobe, Absence of quadrant lobe, Absence of fissure for ligamentum teres, Bilobed caudate lobe and classified according to Netter’s classification.Out of 75 embalmed human liver 23 (30.67%) livers were normal and 52 (69.33%) livers shown one or more than one morphological variation of liver. Out of 52 liver found abnormal fissures were in 23 (30.67), pons hepatis in 2 (2.66%), riedel’s lobe in 3 (4%), absence of quadrant lobe in 1(1.33%) deep renal impression and corset constriction observed in 15 (20%) specimens of liver, diaphragmatic deep groove were observed in 1 (1.33%) specimen. The presence of knowing extra lobes and fissure lies in the fact that might help to interpretation during imaging of hepatobilliary system and may intern lead to surgical implication in operation theater.